2022
DOI: 10.3390/ijms232113088
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Anti-Biofilm and Anti-Quorum Sensing Activities of the β-Adrenoreceptor Antagonist Atenolol against Gram-Negative Bacterial Pathogens

Abstract: The development of bacterial resistance to antibiotics is an increasing public health issue that worsens with the formation of biofilms. Quorum sensing (QS) orchestrates the bacterial virulence and controls the formation of biofilm. Targeting bacterial virulence is promising approach to overcome the resistance increment to antibiotics. In a previous detailed in silico study, the anti-QS activities of twenty-two β-adrenoreceptor blockers were screened supposing atenolol as a promising candidate. The current stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 108 publications
0
28
0
Order By: Relevance
“…25−30 The ability of β-adrenoreceptor antagonists or blockers to inhibit the QS system has been demonstrated by previous studies. 13,14,31 However, the target of QS suppression was not been identified.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25−30 The ability of β-adrenoreceptor antagonists or blockers to inhibit the QS system has been demonstrated by previous studies. 13,14,31 However, the target of QS suppression was not been identified.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Dronedarone blocks potassium, sodium, and L-type calcium currents and exerts antiadrenergic effects by noncompetitive binding to β-adrenergic receptors . However, when nonantibiotic drugs are used as antibiotic potentiators, their mechanisms of action are usually different from their original pharmacological effects. The ability of β-adrenoreceptor antagonists or blockers to inhibit the QS system has been demonstrated by previous studies. ,, However, the target of QS suppression was not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, adrenoreceptor antagonists were screened for their anti-QS and anti-virulence activities [ 31 , 32 ]. Interestingly, β-adrenoreceptor antagonists atenolol and metoprolol diminished the virulence of Pseudomonas aeruginosa, Proteus mirabilis , Serratia marcescens, Salmonella enterica , and E. coli [ 32 , 60 , 61 ]. In addition, α-adrenoreceptor blocker antagonist terazosin showed significant in vitro and in vivo reduction in S. enterica and P. aeruginosa pathogenesis [ 19 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors proved the ability of atenolol to reduce the biofilm formation, virulence enzyme production and motility and finally its potential to protect infected mice. They concluded that atenolol exerts anti-QS and antivirulence activities and can be used as a complementary/adjuvant anti-infectious drug [ 268 ].…”
Section: Drugs As Antibiotic Alternatives or Complementsmentioning
confidence: 99%